Endocrine Disrupting Chemicals - Hester, R.E. (Royal Society of Chemistry, 2011)
This books reviews the long-term environmental effects of chemical exposure that have long been of concern and, more recently, chemicals which cause changes to the sexual development of exposed organisms.